REMOTE SENSING ANALYSIS OF CARBON DIOXIDE GHG EMISSIONS SUPPORTS REGIONAL ACTION PLANS FOR MITIGATION TO THE IMPACTS OF CLIMATE CHANGE IN SITUBONDO REGENCY - Thohiron, Mochamad; Susilo, Achmadi; Suryaningsih, Dwi Retna; Hassan, Faez Mohamad; Mulyono, Budi; Purnama, Khrisna Ari (International Journal of Multidisciplinary Research and Literature, 2024)
The study aims to inventory and analyze GHG Carbon Dioxide (CO2) emissions to support RAD in the mitigation and adaptation of PI Situbondo Regency. It is hoped that the research output can become input for  Regional Governments in implementative designing mitigation and adaptation actions. The scope of the research in the Situbondo Regency area was six months. The analysis method uses a remote sensing system through exploration of Sentinel-5P satellite data for GHG Carbon Dioxide (CO2) gas numerical spatial data on cloud-based digital platform Java script Google Earth Engine (GEE) and Google Colaboratory Research (GColab) 2023, image digitization and outlasting in QGIS software. Research data is remote sensing data access to the Carbon Dioxide gas datasets Sentinel_5P OFFL_CO Offline, and MOD 11A1.061_Terra LST, and EDG 1km. The results show that the highest CO density variable in 2017 was 116 – 239 g/m2, then decreased to 109 – 227 g/m2 in 2019, and to 66 – 180 g/m2 in 2021. The highest range of LST variables in 2017al was 19 – 39 0 C, then increased to 21 – 40 0 C  in 2019, and in 2021 decreased again to 18 – 38 0 C. Regional variables The highest LST distribution in 2017 and 2019 was relatively the same in each sub-district, namely Situbondo, Panarukan, Panji, Kapongan and Jangkar. CO and LST density variables in 2021 are not correlated, r = 0.1 - 0.3